Regulation of Cell Viability and Anti-inflammatory Tristetraprolin Family Gene Expression in Mouse Macrophages by Cottonseed Extracts - Cao, Heping (Sci Rep, 2020)
Bioactive plant extracts have been used for the prevention and treatment of various diseases. One of the major classes of bioactive compounds is plant polyphenols. Cottonseed ethanol extracts were determined by HPLC-MS analysis to be essentially free of toxic gossypol. The objective of this study was to investigate the effect of cottonseed ethanol extracts on the cytotoxicity and regulation of anti-inflammatory tristrataprolin (TTP) family gene expression in mouse cells. MTT, qPCR and immunoblotting assays tested the effects of cottonseed extracts in mouse RAW264.7 macrophages and 3T3-L1 adipocytes. No cytotoxicity effect was observed in macrophages treated with extracts from the coat or kernel of glanded and glandless cottonseed. Similarly, the viability of mouse adipocytes was not affected by cottonseed extracts. In contrast, gossypol and lipopolysaccharides were toxic to macrophages but not adipocytes under high concentration or long time treatment. Cottonseed extracts exhibited modest effect on TTP family gene expression in macrophages but glandless cottonseed coat extract significantly increased TTP mRNA and protein levels with a magnitude similar to cinnamon and green tea polyphenol extract and insulin. These results demonstrated that cottonseed extracts are harmless towards the mouse cells and that glandless cottonseed coat extract stimulates TTP gene expression. We propose that glandless cottonseed is a safe source of plant polyphenols with anti-inflammatory property.